AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING DESCRIPTIVE TEXT AT THE TENTH GRADE OF SMA IT TEBUIRENG 4 AL-ISHLAH - Virani; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
Writing is a fundamental yet challenging skill in English language learning, particularly in producing descriptive texts that require grammatical accuracy, appropriate vocabulary, and correct mechanical conventions. Although error analysis plays an important role in improving writing instruction, studies examining Indonesian EFL learners’ descriptive writing using combined analytical frameworks remain limited. This study aimed to identify the types of errors made by tenth-grade students at SMAIT Tebuireng 4 Al-Ishlah and determine the most dominant error types. This study employed a descriptive qualitative design involving 96 students selected through random sampling. Students’ descriptive texts were analyzed using Dulay et al.’s surface error taxonomy: omission, addition, misformation, and misordering and Brown and Abeywickrama’s writing indicators: content, organization, grammar, vocabulary, mechanics, and style. The findings revealed 1,993 total errors. Misformation was the most dominant surface error (15.25%), followed by omission (11.14%), misordering (7.83%), and addition (4.21%). Meanwhile, mechanics errors were the most frequent writing quality problem (15.20%), followed by grammar (12.74%) and vocabulary (11.04%). The findings indicate that students mainly experience difficulties in grammatical accuracy, verb usage, spelling, capitalization, and vocabulary selection rather than idea development. Therefore, teachers are recommended to provide more focused instruction on grammar, writing conventions, vocabulary development, and the generic structure of descriptive text.